Association of facet orientation and tropism with lumbar disc herniation - H. R., Deepak; Shetty, Karan; G., Lakshmi Narayana Reddy (International Journal of Research in Orthopaedics, 2020)
Background: Intervertebral disc herniation is a degenerative lumbar disease and a common pathology of skeletal system. Currently, most experts assume that facet tropism may affect lumbar degenerative diseases. Considering the previous inconsistent findings on the relationship of facet tropism, the present study was aimed to find the association between facet tropism and lumbar disc herniation. Methods: Patients with low back pain attending the OPD of orthopaedics department, with signs and symptoms of disc herniation were sent for magnetic resonance imaging (MRI). 72 patients with single level disc herniation were included in the study. Facet angles were measured using MRI of 1.5 T using the method described by Karacan et al. Facet tropism was defined as difference of 100 or more in facet joint angles between right and left sides. Results: 45 of the 72 cases (50%) who presented with lumbar disc herniation (LDH) had tropism while none (0%) at the control level did. This association was not statistically significant (p=0.983). Significant association was found between the side of disc herniation and the distribution of the more coronal or sagittal facing facet (p=0.024). Conclusions: Despite the presence of tropism only in the intervertebral segments affected with LDH in our study, the association between tropism and LDH was not statistically significant.